Synthesis and Characterization of NiMo Catalysts Supported on Fine Carbon Particles for Hydrotreating: Effects of Metal Loadings in Catalyst Formulation - Aryee, Emma; Dalai, Ajay Kumar; Adjaye, John (Frontiers in Chemical Engineering, 2022)
The by-products collected during the synthesis of carbon nanohorns (CNH) via the arc discharge synthesis method is comprised of other carbon particles (OCP). At a hydrotreating operating temperature of 370 oC, preliminary investigations using a bimetallic catalyst with support originating from the fine fractions of other carbon particles (OCPf) and containing 13 wt% Mo and 2.5 wt% Ni resulted in an HDS and HDN conversion of 78% and 25%, respectively. Variation of metal compositions in catalyst formulation and its impact on hydrotreating activity was therefore considered in this study to enhance the hydrotreating activity of OCPf –supported catalyst, and to determine if the best NiMo/OCPf catalyst achieved from this study could be a viable catalyst for hydrotreating applications. The co-incipient wetness impregnation was used in preparing series of hydrotreating catalysts with Ni and Mo loadings within the range of (2.5 - 5.0 wt%) and (13-26 wt%) respectively. Overall, the catalyst samples with maximum Ni loading of 5.0 wt% and Mo loadings of either 13 or 19 wt% showed higher dispersion and the ability to form a Type-II Ni-Mo-S phase with enhanced activity. The effects of metal compositions on both HDS and HDN activities were correlated with their physicochemical properties.